2023
DOI: 10.3390/plants12040803
|View full text |Cite
|
Sign up to set email alerts
|

CuO Nanoparticle-Mediated Seed Priming Improves Physio-Biochemical and Enzymatic Activities of Brassica juncea

Abstract: The use of nanoparticles (NPs) in agricultural fields has risen to a level where people are considering NPs as an alternative to commercial fertilizers. The input of copper oxide NPs (CuO NPs) as seed primers was investigated in this study, and the growth indices of Brassica juncea such as phenotypic parameters, photosynthetic attributes, and biochemical parameters were measured during maximum vegetative growth stage, i.e., at 45 days after sowing. Surface sterilized seeds were soaked in varying concentrations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 70 publications
2
6
0
Order By: Relevance
“…Previous studies have reported similar results to our findings on the seedling biomass accumulation of SeO NPs-treated wheat seeds [51]. Likewise, beneficial effects of ZnO NPs, CuO NPs, and FeO NPs on plant biomass accumulation was also reported by [52][53][54], respectively. Moreover, Chau et al [43] also reported a significant increase in dry biomass of soybean due to seed priming with Co and MoO 3 NPs.…”
Section: Resultssupporting
confidence: 91%
“…Previous studies have reported similar results to our findings on the seedling biomass accumulation of SeO NPs-treated wheat seeds [51]. Likewise, beneficial effects of ZnO NPs, CuO NPs, and FeO NPs on plant biomass accumulation was also reported by [52][53][54], respectively. Moreover, Chau et al [43] also reported a significant increase in dry biomass of soybean due to seed priming with Co and MoO 3 NPs.…”
Section: Resultssupporting
confidence: 91%
“…Increased concentrations of total phenols were found also in buckwheat exposed to metals, such as Zn and Al [54,56], and seeds treated with 2% chlorcholine chloride [57]. Furthermore, the seed coating of Brassica juncea with CuO NPs had a 41% increase in proline content, which is also an indicator of antioxidant non-enzymatic activity [15]. Altogether, our results confirm the role of phenylpropanoid metabolic pathways in the response of plants to metal or/and metallic NPs [15,58].…”
Section: Phenolic Metabolites In Treated Seedlingssupporting
confidence: 62%
“…Furthermore, the seed coating of Brassica juncea with CuO NPs had a 41% increase in proline content, which is also an indicator of antioxidant non-enzymatic activity [15]. Altogether, our results confirm the role of phenylpropanoid metabolic pathways in the response of plants to metal or/and metallic NPs [15,58]. This suggests that CuO NPs and MPs at appropriate concentrations could protect plants from stress by boosting their antioxidative defense system and may also contribute additional nutritional value to human nutrition.…”
Section: Phenolic Metabolites In Treated Seedlingsmentioning
confidence: 99%
See 2 more Smart Citations